La spesa pubblica nel XX secolo Una prospettiva globale - Tanzi, Vito (Firenze University Press, 2007)
The volume deals with the changing role of public finance over the course of the twentieth century, documenting the enormous increase in public spending found in all industrialised countries. The authors believe that the increase in government spending over the past thirty-five years has not resulted in significant additional social and economic well-being. This suggests that public spending in industrialised countries could be much lower without sacrificing important economic policy objectives. For this to be possible, governments must reconsider their role as players who set the rules of the game, and this study suggests possible institutional and spending policy reforms. After a detailed account of the experiences of reforms in different countries and the related debate, the volume closes with a perspective on the future role of the state in an era in which globalisation could demand, and people might want, "leaner" but by no means more inefficient states. Press review: VISUM, March 2009: Economic growth and public spending